Macroevolutionary Analyses Provide New Evidence of Phasmid Wings Evolution as a Reversible Process. (11th June 2022) - Forni, Giobbe; Martelossi, Jacopo; Valero, Pablo; Hennemann, Frank H; Conle, Oskar; Luchetti, Andrea; Mantovani, Barbara
Abstract: The concept that complex ancestral traits can never be recovered after their loss is still widely accepted, despite phylogenetic and molecular approaches suggest instances where phenotypes may have been lost throughout the evolutionary history of a clade and subsequently reverted back in derived lineages. One of the first and most notable examples of such a process is wing evolution in phasmids; this polyneopteran order of insects, which comprises stick and leaf insects, has played a central role in initiating a long-standing debate on the topic. In this study, a novel and comprehensive time tree including over 300 Phasmatodea species is used as a framework for investigating wing evolutionary patterns in the clade. Despite accounting for several possible biases and sources of uncertainty, macroevolutionary analyses consistently revealed multiple reversals to winged states taking place after their loss, and reversibility is coupled with higher species diversification rates. Our findings support a loss of or reduction in wings that occurred in the lineage leading to the extant phasmid most recent common ancestor, and brachyptery is inferred to be an unstable state unless co-opted for nonaerodynamic adaptations. We also explored how different assumptions of wing reversals probability could impact their inference: we found that until reversals are assumed to be over 30 times more unlikely than losses, they are consistently inferred despite uncertainty in tree and model parameters. Our findings demonstrate that wing evolution is a reversible and dynamic process in phasmids and contribute to our understanding of complex trait evolution. [Dollo's law; Phasmatodea; phylogenetic comparative methods; polyneoptera; reversals; wing.]